International Legal and Instiutional Mechanisms for Combating Corruption - Zaher, Animar Ali (Journal of Economic, Administrative and Legal Sciences, 2025)
This research explores international efforts to combat corruption, emphasizing that corruption is a global challenge that threatens development and stability. It defines corruption, its types, and causes, highlighting its negative effects on societies and economies. The study discusses international anti-corruption agreements, particularly the United Nations Convention against Corruption (UNCAC), which aims to promote transparency and accountability in both public and private sectors.Additionally, the research examines the role of international organizations, such as the World Bank and the International Monetary Fund, in implementing anti-corruption policies and measures. These include promoting good governance, strengthening oversight mechanisms, and supporting judicial systems. The study also presents successful examples from various countries that have adopted effective anti-corruption strategies, such as utilizing technology in government processes and increasing public awareness of rights.In conclusion, the study emphasizes the importance of international cooperation in combating corruption. It calls for strengthening integrity, enforcing deterrent penalties, and fostering a culture of transparency and accountability to ensure a stable economic and political environment.
Keywords: Corruption; Transparency; Accountability; Good Governance; United Nations; Anti-Corruption; International Conventions; Integrity